2018
DOI: 10.1158/0008-5472.can-17-1733
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Blocking Protein Neddylation in T315I-BCR-ABL Leukemia Cells and Leukemia Stem Cells

Abstract: Imatinib revolutionized the treatment of chronic myeloid leukemia (CML), but drug resistance and disease recurrence remain a challenge. In this study, we suggest a novel strategy based on blocking protein neddylation to address BCR-ABL point mutations and leukemia stem cells (LSC) that lie at the root of imatinib-resistant recurrences. On the basis of the finding that the NEDD8-activating enzyme subunit NAE1 is overexpressed in CML cells, we hypothesized that the function of certain neddylation-dependent prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 47 publications
5
28
2
Order By: Relevance
“…We show that the CHK1 kinase inhibitor AZD7762 had an almost perfect additive effect in combination with MLN4924 ( Fig S3), suggesting that CHK1 and Nedd8-conjugation act in the same pathway that prevents replication stress in Ph+ leukemia cells. These findings are in good agreement with a recent study in which it was shown that MLN4924 induces DNA damage as reflected by accumulation of CDT1, γH2AX and phospho-Chk2 [47].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We show that the CHK1 kinase inhibitor AZD7762 had an almost perfect additive effect in combination with MLN4924 ( Fig S3), suggesting that CHK1 and Nedd8-conjugation act in the same pathway that prevents replication stress in Ph+ leukemia cells. These findings are in good agreement with a recent study in which it was shown that MLN4924 induces DNA damage as reflected by accumulation of CDT1, γH2AX and phospho-Chk2 [47].…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrate here that the first-in-class Nedd8activating enzyme inhibitor MLN4924 very efficiently induced cell death of Ph+ leukemia cells, surpassing the effect in MM cells, for which MLN4924 is currently under investigation in a phase I/II clinical trial [39]. In line with previous data [47] we showed that MLN4924 induced caspase-dependent apoptosis and was equally active in the imatinib-resistant KBM5-T315I subline as in the parental KBM5 cell line, indicating that MLN4924 may be of use for treatment of imatinib-resistant leukemias. Furthermore, we show that MLN4924 sensitized Ph+ cell lines that are characterized by a limited TKI sensitivity for both imatinib and the third generation ABL TKI ponatinib.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations